THE MOTHER TONGUE AS A TOOL OF NATIONAL NARRATIVE AND FOLKLORE IN MODERN LITERATURE - Shukurullayeva Namuna Nabijan's daughter (European Science Publishing, 2024)
This article explores the significance of the mother tongue in modern literature as a medium for preserving and promoting national narratives and folklore. It emphasizes how the mother tongue serves as a repository of a nation's cultural identity, values, and collective memory. Through modern literature, writers draw on the richness of their mother tongue to create narratives that reflect their heritage and national identity, often incorporating folklore to maintain a connection between past and present. The article also highlights how the adaptation of folklore in modern literature allows for the exploration of contemporary social issues while keeping traditional stories relevant. Additionally, the role of translation is discussed, emphasizing its importance in sharing national narratives with a global audience, despite the challenges of preserving linguistic nuances. The article concludes by noting how literature in endangered languages contributes to the preservation of both linguistic and cultural heritage, ensuring the continuity of national identity.
Keywords: mother tongue, national narrative, folklore, modern literature, cultural identity, oral tradition, indigenous languages, translation, endangered languages, storytelling, post-colonial literature, national heritage, literary preservation.